The Relation of Severity and Comorbidity to Treatment Outcome with Cognitive Behavioral Therapy for Childhood Anxiety Disorders - Liber, Juliette Margo (Springer US, 2010)
The present study investigated the impact of comorbidity over and above the impact of symptom severity on treatment outcome of Cognitive Behavioral Therapy for children with anxiety disorders. Children (aged 8–12, n = 124) diagnosed with an anxiety disorder were treated with a short-term CBT protocol. Severity was assessed with a composite measure of parent-reported behavior problems. Two approaches to comorbidity were examined; “total comorbidity” which differentiated anxiety disordered children with (n = 69) or without (n = 55) a co-occurring disorder and “non-anxiety comorbidity’ which differentiated anxious children with (n = 22) or without a non-anxiety comorbid disorder (n = 102). Treatment outcome was assessed in terms of Recovery, represented by post-treatment diagnostic status, and Reliable Change, a score reflecting changes in pre- to post-treatment symptom levels. Severity contributed to the prediction of (no) Recovery and (more) Reliable Change in parent-reported internalizing and externalizing symptoms and self-reported depressive symptoms. Total and non-anxiety comorbidity added to the prediction of diagnostic recovery. Non-anxiety comorbidity added to the prediction of Reliable Change in parent reported measures by acting as a suppressor variable. Non-anxiety comorbidity operated as a strong predictor that explained all of the variance associated with severity for self-reported depressive symptoms. The results support the need for further research on mechanisms by which treatment gains in children with higher symptom severity and non-anxiety comorbidity can be achieved.